Market and non-market labor supply and recent German tax reform impacts: Behavioral response in a combined dynamic and static microsimulation model - Joachim Merz (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1993)
This study on market and non-market labor supply and taxes is based on a theoretical microeconomic model with multiple labor supply in the formal and informal economy. This multiple time allocation model, which explicitly takes into account taxes, transfer payments, socioeconomic characteristics of the individual and the household, is specified in a multiple three-stage approach explaining the participation probability, the relevant wages and the hours of work in different activities. Uncompensated and compensated elasticities on market and non-market labor supply are computed. The estimates are based on data from the enlarged Sfb 3-Secondary Occupation Survey 1984, enlarged by tax and regional information for the economic situation and labor demand consideration. This microanalysis will follow the substantial question whether incentive or disincentive labor supply effects of the 1990 German tax reform are to be expected. The recent German Tax reform impacts are quantified by a combined dynamic and static microsimulation approach based on microeconometric estimated behavioral pattern representative for the Federal Republic of Germany. – – Diese Studie über markt- und nichtmarktmäßiges Arbeitsangebot und Steuern basiert auf einem theoretischen mikroökonomischen Modell multipler Aktivitäten in der formellen und informellen Ökonomie. Dieses multiple Zeitallokationsmodell, das explizit Steuern, Transferzahlungen und soziökonomische Charakteristika enthält, wird in einem multiplen dreistufigen mikoökonometrischen Ansatz spezifiziert, der die Partizipationswahrscheinlichkeit, die relevanten Lohnsätze und die Arbeitszeit in den verschiedenen Aktivitäten erklärt. Unkompensierte und kompensierte Elastizitäten markt- und nichtmarktmäßiger Aktivitäten werden berechnet. Die selektionskorrigierten Schätzungen basieren auf Mikrodaten der Sfb 3- Nebenerwerbstätigkeitsumfrage, die um Regionaldaten zur ökonomischen Situation und der Arbeitsnachfrage sowie um spezifische Steuerinformationen aus dem Sozio-ökonmischen Panel erweitert wurden. Diese Mikroanalyse folgt der substantiellen Frage, ob Anreizwirkungen der bundesrepublikanischen Steuerreform von 1990 erwartet werden können. Die kombinierte dynamische und statistische Mikrosimulationsanalyse, mit für die Bundesrepublik repräsentativen Daten, basiert auf den mikroökonometrisch geschätzten individuellen Verhaltensweisen.
Keywords: C80; C81; J20; J22; H24; H26; D13; 330; behavioural effects; Steuerreformeffekte; Verhaltensreaktion; kombinale und statistische Mikrosimulation